A Late Glacial and Holocene sugar biomarker-based δ18O paleoclimate record from the Afro-alpine Central Lake, Bale Mountains, Ethiopia - Samuel G. Chernet; Lucas Bittner; Graciela Gil-Romera; Bruk Lemma; Marcel Bliedtner; Roland Zech; Bruno Glaser; Tobias Bromm; Sönke Szidat; Wolfgang Zech; Michael Zech (Global and Planetary Change, 2025)

Distribution and habitat use by the Audouin's Gull (Ichthyaetus audouinii) in anthropized environments - Aleix Ferrer Vilaplana; Isabel Afán; Daniel Oro; Juan Bécares; Marc Illa; Marcel Gil; Albert Bertolero; Manuela G. Forero; Francisco Ramírez (Science of The Total Environment, 2024)

Across the firefly-verse: comparison of niche suitability of an exotic firefly in its native and colonized range - Diego Gil-Tapetado; Marcel Koken; Raphaël De Cock; Jose F. Gómez; Francisco José Cabrero-Sañudo; Carlo Polidori (Journal of Insect Conservation, 2024)
Photinus signaticollis Blanchard, 1846 (Coleoptera: Lampyridae) is a firefly native to South America and recently established in Europe. Since 2016, this firefly has colonized the northeastern part of the Iberian Peninsula and crossed the Pyrenees to reach southern France in 2019. The larvae of this firefly feed on earthworms, so a high density of this species could negatively impact this key group in soil processes and agriculture. The precise extent of colonization, the environmental niche and the potential range expansion in non-native areas are currently unknown. Using species distribution models, we have found the high suitability areas across Europe where P. signaticollis may become established if introduced. Interestingly, using only South American records and associated conditions modelling it can be strongly predicted where the species is currently found in Europe. Despite a few propagules of P. signaticollis detected in very unsuitable areas of Spain were no longer detected after their initial observation, the climatic niche overlap between South America and Europe populations appeared to be very low. In our case, this pattern is more likely to reflect a high unfilled niche rather than a niche expansion or niche shift, because many occupied areas in South America possess a climate not occurring in Europe. Among the considered variables, we furthermore found that only the temperature seasonality appeared to be the same in both native and European areas and relevant in the models, suggesting that it may represent the main limiting factor for establishing this firefly.

Gut microbiota shifts in the giant tiger shrimp, Penaeus monodon, during the postlarvae, juvenile, and adult stages - Francesco Cicala; Asunción Lago-Lestón; Bruno Gomez-Gil; Teresa Gollas-Galván; Jennyfers Chong-Robles; Edilmar Cortés-Jacinto; Marcel Martínez-Porchas (Aquaculture International, 2020)

Lamprospora densireticulata sp. nov., L. dictydiola and L. carbonicola (Pyronemataceae, Pezizales)—three very similar species from very different hosts and habitats - Marcel Vega; Lukáš Janošík; Zuzana Sochorová; Rubén Martínez-Gil; Jan Eckstein (Mycological Progress, 2019)

Combination of multiple neural crest migration assays to identify environmental toxicants from a proof-of-concept chemical library - Johanna Nyffeler; Xenia Dolde; Alice Krebs; Kevin Pinto-Gil; Manuel Pastor; Mamta Behl; Tanja Waldmann; Marcel Leist (Archives of Toxicology, 2017)

Dynamics of inhibitory co-transmission, membrane potential and pacemaker activity determine neuromyogenic function in the rat colon - Noemí Mañé; Víctor Gil; Míriam Martínez-Cutillas; María Teresa Martín; Diana Gallego; Marcel Jiménez (Pflügers Archiv - European Journal of Physiology, 2014)

Estimating the complexity of bird song by using capture-recapture approaches from community ecology - Lszl Z. Garamszegi; Thorsten J. S. Balsby; Ben D. Bell; Marta Borowiec; Bruce E. Byers; Tudor Draganoiu; Marcel Eens; Wolfgang Forstmeier; Paolo Galeotti; Diego Gil; Leen Gorissen; Poul Hansen; et al. (Behavioral Ecology and Sociobiology, 2005)

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)